RESPON MURID DALAM PEMBELAJARAN STRATEGI SCAFFOLDING BERBASIS STEAM PADA MATERI GERHANA - Callista Putri, Angelia Pinky; Subekti, Hasan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe how students behave when STEAM-based scaffolding strategies are applied to eclipse-related material. This study employs a quantitative descriptive method and is grounded in the importance of using creative learning approaches that can enhance students’ interest, perceived relevance, and self-confidence in science learning. Data collection employed a Likert-scale questionnaire consisting of 18 statements covering three indicators: students’ interest in learning, the relevance of learning to their own lives, and students’ self-confidence. The research subjects were students in Class VII C. To identify trends in student responses, the data were analyzed using percentage calculations. The results of the study indicate that the majority of students provided positive responses, dominated by the “agree” and “strongly agree” categories across all indicators. This suggests that STEAM-based scaffolding strategies are effective in creating interactive, contextual, and student-centered learning. These strategies can also enhance students’ understanding of concepts and boost their self-confidence during the learning process.